ATRIAL FIBRILLATION INFLUENCES AUTOMATIC OSCILLOMETRIC ANKLE-BRACHIAL INDEX MEASUREMENT. (June 2018) - Sinski, M.; Lewandowski, J.; Szmigielski, C.; Dabrowski, M.
Abstract : Objective: The ABI (ankle - brachial index) repeated measurements using Doppler method were shown to be accurate despite atrial fibrillation (AF). However, they require expertise and are time consuming. Automatic oscillometric devices can be effective in ABI, but their accuracy during AF is unknown. The purpose of the study was to investigate whether AF influences ABI obtained with automatic oscillometric method. Design and method: Ninety-nine patients (age 66.6 ± 11 years, M/F - 63/36) who underwent AF electrical cardioversion (EC) were investigated. ABI measurements using oscillometric and Doppler methods were performed on both lower extremities (198 cases) before and after EC. Results: The ABI measured using oscillometric method on both lower limbs didn't change after EC (1.21 [1.13–1.27] vs. 1.22 [1.14–1.26], p = 0.664, respectively). Correlation was found between measurements performed with oscillometric method before and after EC (r = 0.49, p < 0.001). ABI measured before and after EC using Doppler and oscillometric method showed significant difference (1.14 [1.07–1.22] vs. 1.21 [1.13–1.27], p < 0.001; and 1.18 [1.09–1.13] vs 1.22 [1.14–1.26], p < 0.001 respectively). Upper 95% CI margins for the median of difference in ABI between methods were 0.08 and 0.06 before and after EC and the difference was higher during AF than during sinus rhythm (0.07 vs 0.04, p = 0.002). That may be significant from clinical perspective suggesting clinical significance. Both methods showed week correlation before EC (r = 0.35, p < 0.001) and lack of correlation after EC (r = 0.12, p = 0.07). The Bland-Altman plot showed poor agreement between measurements performed with the Doppler and oscillometric method in sinus rhythm and during AF. ROC analysis revealed AUC of 0.57 (95% CI: 0.10–1) with 1.39 oscillometric cut-off for sensitivity (0.5) and specificity (0.96). Conclusions: The study results show, that atrial fibrillation can has an impact on ABI measurements performed with the oscillometric method. Therefore, we postulate, that the automated oscillometric method should not replace the reference Doppler method in patients with atrial fibrillation.